Embodied, embedded or both? Investigating experts and expertise in two Greater Boston social movements. - Frickel, Scott; Porcelli, Apollonya; Teller, Amy; Niznik, Aaron (Social Movement Studies, 2024)
This study employs quantitative and qualitative data from a large diverse sample of scientists and professionals active in Greater Boston's environmental and community development movements to pursue two lines of inquiry regarding experts and expertise in social movements. Statistical analysis and supporting qualitative analysis investigate, first, the extent to which expert's professional training and employment predict their mobilization into different social movements (a measure of embodied expertise) and, second, the more specific ways that experts' embeddedness in Boston-area businesses, law firms, and colleges and universities provide distinct mobilization pathways. Finding support for both, our conclusions emphasize the strategic value and heterogeneity of expert activists as a group and the importance of institutional analysis in understanding the dynamics and impacts of expert activism.